MACAM-MACAM HADIS DARI SEGI KUALITASNYA - Miftahul Huda (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The division of hadith is a fundamental aspect of hadith studies that has long attracted the attention of scholars. This article explores the various types of hadith divisions in the Islamic tradition and examines the relevance and sustainability of these approaches in the context of modern science. The hadith of the Prophet Muhammad, as the second guide to life after the Qur'an, plays an important role when the Qur'an does not provide clear legal provisions. This study aims to summarize and evaluate the contributions of previous studies and offer new insights in understanding the development of hadith division studies in the future. The main focus of this article is the analysis of various methods of hadith classification, both in terms of sanad and matan, and their methodological implications. The research method used is a literature review involving the discovery, analysis, and synthesis of relevant literature on hadith division. Data were collected from scientific articles, books, journals, and other publications that discuss hadith division. This article discusses various types of hadith, including sahih, hasan, and daif hadith. An authentic hadith is defined as a hadith that meets the strict requirements of sanad and matan, namely continuous sanad, fair and habitual narrators, and free from irregularities and defects ('illat). Sahih hadiths are divided into two categories: authentic li-dzatih (authentic in itself) and authentic li-ghairih (authentic due to the support of other hadiths). Hasan hadith, which is defined as a hadith narrated by a fair narrator with less strong memorization but muttasil sanad, is also divided into hasan li-dzatih and hasan li-ghairih. Dhaif hadith, which do not meet the requirements of authentic and hasan hadith, are grouped based on the quality of sanad and matan, and are divided into mauquf hadith (narrated from friends) and maqtu' (narrated from tabi'in). The conclusion of this article confirms that authentic, hasan, and dhaif hadith have an important role in hadith science. Sahih hadith is the most valid and widely accepted type of hadith, while hasan hadith can still be accepted with some limitations. Daif hadith, although it does not meet the strict requirements of sahih and hasan hadith, still has value in certain contexts and can be used with caution, especially in terms of charitable motivations.